2013
DOI: 10.1136/bjsports-2012-092061
|View full text |Cite
|
Sign up to set email alerts
|

Examining injury risk and pain perception in runners using minimalist footwear

Abstract: Running in minimalist footwear appears to increase the likelihood of experiencing an injury, with full minimalist designs specifically increasing pain at the shin and calf. Clinicians should exercise caution when recommending minimalist footwear to runners otherwise new to this footwear category who are preparing for a 10 km event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(131 citation statements)
references
References 25 publications
4
119
1
7
Order By: Relevance
“…16 If minimalist shoes do not affect running gait at the fast running speeds that are common to race distances that feature minimalist shoes, runners could be risking injury for no benefit. 10,11 Therefore, the primary purpose of our study was to determine if wearing minimalist shoes instead of conventional shoes caused runners to change foot-strike pattern and joint work at a fast running speed (18 km/h). We hypothesized that more runners would change from a rearfoot foot strike (RF) to a midfoot foot strike (MF) or forefoot foot strike (FF) when running in minimalist shoes compared with conventional shoes.…”
mentioning
confidence: 99%
“…16 If minimalist shoes do not affect running gait at the fast running speeds that are common to race distances that feature minimalist shoes, runners could be risking injury for no benefit. 10,11 Therefore, the primary purpose of our study was to determine if wearing minimalist shoes instead of conventional shoes caused runners to change foot-strike pattern and joint work at a fast running speed (18 km/h). We hypothesized that more runners would change from a rearfoot foot strike (RF) to a midfoot foot strike (MF) or forefoot foot strike (FF) when running in minimalist shoes compared with conventional shoes.…”
mentioning
confidence: 99%
“…Instead, the smaller improvement in our study could be due to the lower total exposure to minimalist shoes (3.5 hours) compared to previous studies (5 hours). 7 Several different methods for transitioning to minimalist shoes have been described in the literature 7,25,26 but there is currently no clinical standard. Increased lower limb pain and injury risk has been reported for runners transitioning to more than 50% of weekly running in minimalist shoes over 12 weeks 26 and increased bone marrow edema has been reported in runners who do not following a prescribed introduction to minimalist shoes during 10 weeks of running.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lighter weight, minimal shoes are related to increased risk of injury in runner (Salzler et al 2012b;Ryan et al 2013). Specifically, Ryan et al (Ryan et al 2013) reported on 99 recreational runner training for a 10 km event.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lighter weight, minimal shoes are related to increased risk of injury in runner (Salzler et al 2012b;Ryan et al 2013). Specifically, Ryan et al (Ryan et al 2013) reported on 99 recreational runner training for a 10 km event. Upon completion of the training, those runners training in the traditional "neutral" shoe reported the fewest amount of injuries compared with the partial minimalist and minimalist shoe.…”
Section: Discussionmentioning
confidence: 99%